Implementation of the creative response project model to improve student learning outcomes - Agnestina, Dewi Sandriya; Arisni Kholifatu Amalia Shofiani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Education which is very closely related to learning activities, where the learning process involves various supporting elements ranging from students to teachers. Learning in which the process of interaction and the process in which a teacher will be the party who imparts knowledge while students are the parties who receive knowledge. Learning activities must make students feel comfortable with it so that the knowledge conveyed will be well received . One of the things that can be done is to apply an innovative learning model, as is the case with the creative response project learning model . Where this learning model has its own charm for students, because students will be more likely to capture what they see and hear, rather than just what they see or hear. In that case students will be more active in learning because in this creative response project model the students are more active, in using this creative response project learning model you can also see the increased learning outcomes of students, and the responses of students who are so very enthusiastic. The goal to be achieved from the implementation of this research is to describe student responses, student activities, and student learning outcomes by applying the creative response project learning model. This type of research is a quantitative descriptive research. The sample taken in this study was class IX at SMP Negeri 1 Diwek, Jombang Regency. With a population of class IX F with a total of 28 students. The data collection techniques used were questionnaires, observation sheets, and question sheets which included pretest and posttest . Based on the results of the analysis which shows that: 1) The students' response to the lesson is classified as positive with a percentage of more than 50% in a classical manner. 2) student activity is classified as very active with a classical percentage of 86.18%. 3) the learning outcomes of students achieve 100% completeness classically with an average grade of 92.67